2021
DOI: 10.1002/ijfe.2496
|View full text |Cite
|
Sign up to set email alerts
|

The environmental consequences of blockchain technology: A Bayesian quantile cointegration analysis for Bitcoin

Abstract: During recent years, there is a widespread belief among researchers and academicians that the Bitcoin usage is imposing an additional burden on the environment inducing climate change.Although several studies have focused on issues related to the energy consumption of the basic cryptocurrencies, an open question remains regarding the environmental depiction of the Bitcoin. By resorting to Bayesian analysis and quantile cointegrated vector autoregression (CQVAR) model techniques, this study seeks to disentangle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Lastly, there is a lot of attention regarding Bitcoin's carbon footprint, with many researchers providing evidence of Bitcoin's negative impact on the environment. Authors such as Di Febo et al (2021) and Polemis and Tsionas (2021) suggest that miners could be incentivized to use clean energy sources. We highly disagree with this proposal as there is clearly not enough justification for it.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lastly, there is a lot of attention regarding Bitcoin's carbon footprint, with many researchers providing evidence of Bitcoin's negative impact on the environment. Authors such as Di Febo et al (2021) and Polemis and Tsionas (2021) suggest that miners could be incentivized to use clean energy sources. We highly disagree with this proposal as there is clearly not enough justification for it.…”
Section: Discussionmentioning
confidence: 99%
“…Di Febo et al (2021) found the relation of Bitcoin price and carbon credits to be only in one direction and greater in downside quantiles as compared to the upside, suggesting an extreme carbon market behaviour in times of elevated risk in Bitcoin, i.e., asymmetric reaction patterns with respect to Bitcoin gains and losses. A study from Polemis and Tsionas (2021) focusing on the effects of Bitcoin miners' revenue on carbon dioxide emissions revealed that miners' revenue negatively affects environmental degradation.…”
Section: Electricity Consumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a recent analysis by Jiang et al (2021), maintaining the Bitcoin block chain in 2024 will require 296.59 Twh, leading to producing 130.50 million metric tons of carbon. Polemis and Tsionas (2021) conducted an investigation in 50 countries to find the causal relationship among Bitcoin usage and Co2 emissions. Surprisingly, lower Bitcoin miner returns have a rapid effect on environmental circumstances.…”
Section: Literature Reviewmentioning
confidence: 99%